A comparison of Islamic religious practices in Pakistan and Indonesia: A sociocultural perspective - Wijianto, Diski Wahyu; Arini Nur Yunia Puspitaningrum Rahmwati; Hidayah Kurniawati; Peni Indrayudha; Tri Yulianti; Ahwan Abdul; Muhammad Ajmal Shah (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2024)
Islam is the majority religion in both Pakistan and Indonesia, the two countries with the largest Muslim populations in the world. While both uphold Islam as the primary faith, religious practices in each country are influenced by differing historical, social, and cultural contexts. This article compares Islamic religious practices in these two nations from a socio-cultural perspective. The research method utilized includes a lecture delivered by Assist. Prof. Muhammad Ajmal Shah, an academic and practitioner from Pakistan. The analysis covers various aspects, such as the size of the Muslim population, the application of Sharia law, variations in Islamic sects and practices, and the interplay between religion and politics. The findings indicate that in Pakistan, Islam serves as a foundational basis for policymaking and national identity, with stricter implementation of Sharia law. In contrast, Indonesia integrates Islamic law with customary and secular laws within a pluralistic framework. Both countries face challenges in maintaining religious tolerance and social stability amidst globalization and modernization. The study concludes that despite differences in the implementation of Islamic law and politics, religion continues to play a significant role in both countries, presenting challenges and opportunities to uphold societal harmony.